A síndrome metabólica como fator de risco para injúria renal aguda em pacientes com infarto agudo do miocárdio - Bruetto, Rosana Gobi (2017)
Acute myocardial infarction (AMI) is one of the leading causes of death world widely, and acute kidney injury (AKI) is a common complication after admission due to AMI. Metabolic syndrome (MS) is a very prevalent condition in patients with AMI, but data on its influence on the development of AKI in this clinical context are scarce. Objective: To analyze whether MS is a risk factor for the development of AKI in hospitalized patients diagnosed with AMI. Patients and Methods: This is a single-center, cohort, observational study that evaluated patients with AMI from a prospective data bank in order to assess the role of MS as an independent risk factor for the development of AKI. A total of 1,012 patients admitted with acute ST-elevation myocardial infarction (STEMI) and acute non-ST-segment elevation myocardial infarction (non-STEMI) were included. The diagnostic criterion for AKI was the Kidney Disease: Improving Global Outcomes (KDIGO) definition, during the first seven days of hospitalization. The criterion for SM was the Joint Interim Statement (JIS) definition. Results: The diagnosis of AKI occurred in 34% and MS in 68.6% of the total cohort. Patients with MS developed AKI more frequently (38.3% versus 24.5% no MS, p <0.001). In the multivariate analysis MS was not associated with an increased risk of developing AKI. The factors associated with a higher risk of AKI in the multivariate analysis were male gender (odds ratio [OR] 1.50, 95% confidence interval [CI] 1.05-2.13, p=0.023), diabetes, 95% CI 1.33-2.76, p<0.001), anterior wall STEMI (OR 1.50 95% CI 1.04-2.16, p=0.030), use of vasoactive drugs (OR 2.90 95% CI 1.52-5.51, p=0.001) and diuretic therapy (OR 4.41 95% CI 3.10-6.29, p<0.001). Two factors were associated with a lower risk of AKI: coronary angiography (OR 0.35 95% CI 0.25-0.50, p<0.001) and coronary artery bypass graft (OR 0.05 CI 95% 0.02-0.18, p<0.001) performed during the first seven days of hospital staying. Conclusion: MS was not an independent risk factor for the development of AKI after admission due to AMI.